Combined bleaching and hydrolysis for isolation of cellulose nanofibrils from waste sackcloth. (20th October 2015) - Cao, Yang; Jiang, Yaoquan; Song, Yuanyuan; Cao, Shaomei; Miao, Miao; Feng, Xin; Fang, Jianhui; Shi, Liyi
Highlights: A highly efficient approach for preparation of CNF from waste sackcloth. H2 O2 /HNO3 solution was utilized as both bleaching agent and hydrolysis medium. Sonication process was beneficial to form well dispersed colloidal suspensions. CNF with 20–50 nm in width and hundreds of nanometers in length was obtained. Abstract: A convenient and low cost process to prepare cellulose nanofibrils (CNF) from waste sackcloth by using H2 O2 /HNO3 solution as both bleaching agent and hydrolysis medium was recommended. The resultant CNF with high crystallinity was initially synthesized by the chemical disintegration process for the removal of non-cellulosic components and the crystallinity of CNF was 68.11% compared with that of sackcloth fibers (48.28%). The decomposition temperature of CNF was about 340 °C, which indicated that the thermal stability of the fibers was increased after the combined bleaching and hydrolysis. Subsequently, the homogenous CNF colloidal suspensions in water, ethanol and acetone were obtained after sonication treatment. The CNF in water suspensions with 20–50 nm in width and hundreds of nanometers in length was ultimately prepared under the conditions of different ultrasonic time.